Knowledge and practice of hand washing among secondary school students in Otukpo, Nigeria - Elijah Edache Ehoche; Frances Obioma; Lydia Rose Ogwuche (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
High incidence of communicable diseases such as the prevailing COVID-19 pandemic can be prevented with a proper hand washing practice amongst other measures. This cross-sectional survey was designed to access the knowledge and practice of hand washing among secondary school students in Otukpo, Nigeria. This study was conducted among 100 students from four selected secondary schools in Otukpo using a simple random sampling method with informed consents from participants. The data obtained through a questionnaire and observational check list are presented in simple statistical tables. The results of the survey showed that 57% of the respondents got their knowledge from home, 41% and 2% got theirs from school and other sources respectively. Insufficient hand-washing supply (37%), forgetfulness (25%), time pressure (23%) and low level of knowledge on hand-washing (15%) constitute the hindrances to hand-washing by correspondents’ responses. This indicates that the students have average knowledge of hand-washing but showed inefficient practice due to the aforementioned factors. This is relevant with the control of the spread of contagious diseases.